(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
In the context of the global humanization of education, an inclusive approach is becoming a key vector in the development of modern schools. The relevance of this work is due to the need to overcome contradictions between the regulatory requirements for inclusion and the real possibilities of educational organizations in providing high-quality education for children with special educational needs. The transition from the formal presence of a child in the classroom to full-fledged participation in the educational process requires an in-depth analysis of the specifics of pedagogical interaction. The paper reveals the principles of modifying curricula and adapting content to specific nosological groups. The role of assistive technologies and pedagogical support as necessary tools for reducing cognitive load and psychological barriers is substantiated. Methods of creating flexible learning materials that are accessible to all categories of students without the need for excessive specialization are considered. Criteria for assessing the dynamics of the development of not only academic knowledge, but also the life competencies of a child in an inclusive environment are proposed. The author emphasizes that the success of inclusive education depends not only on the material and technical equipment, but also on the professional readiness of teachers to work in a diverse environment. The model of integrated support proposed in the work makes it possible to minimize the risks of social isolation of children with disabilities and contributes to the formation of a tolerant community.